First observation and measurement of the branching fraction for the decay B0s→D∗∓sK± - Aaij, Roel; Aquines Gutiérrez, Osvaldo; Bachmann, Sebastian; Bien, Alexander; Blouw, Johan; Braun, Svende; Britsch, Markward; Comerma-Montells, Albert; De Cian, Michel; Dordei, Francesca; Esen, Sevda; Färber, Christian; et al. (Journal of high energy physics, 2015)
The first observation of the Bs0 → Ds∗∓K± decay is reported using 3.0 fb−1 of proton-proton collision data collected by the LHCb experiment. The Ds∗∓ mesons are reconstructed through the decay chain Ds∗∓ → γDs∓(K∓K±π∓). The branching fraction relative to that for Bs0 → Ds∗−π+ decays is measured to beℬBs0→Ds∗∓K±/ℬBs0→Ds∗−π+=0.068±0.005−0.002+0.003, where the first uncertainty is statistical and the second is systematic. Using a recent measurement of ℬBs0→Ds∗−π+, the absolute branching fraction of Bs0 → Ds∗∓K± is measured asℬBs0→Ds∗∓K±=16.3±1.2stat−0.5+0.7syst±4.8norm×10−5, where the third uncertainty is due to the uncertainty on the branching fraction of the normalisation channel.
Im Titel sind "∓" und "±" hochgestellt
Im Titel sind "0" und "s" untereinander geschrieben: "0" hochgestellt, "s" tiefgestellt
Im Titel sind "∗" und "s" untereinander geschrieben: "∗" hochgestellt, "s" tiefgestellt
The LHCb Collaboration: R. Aaij, O. Aquines Gutierrez, B. Adeva, M. Adinolfi, S. Bachmann, A. Bien, J. Blouw, S. Braun, M. Britsch, A. Comerma-Montells, M. De Cian, F. Dordei, S. Esen, C. Faerber, M. Fontana, D. Gerick, E. Gersabeck, L. Grillo, X. Han, S. Hansmann-Menzemer, A. Jaeger, M. Kolpin, K. Kreplin, G. Krocker, B. Leverington, J. Marks, M. Meissner, D.S. Mitzel, J. Neubert, M. Neuner, T. Nikodem, M. Schmelling, P. Seyfert, M. Stahl, S. Stahl, U. Uwer, M. Vesterinen, R. Waldi, S. Wandernoth, D. Wiedner, A. Zhelezov [und 660 weitere]
Gesehen am 23.11.2020